IMPLEMENTASI CASE METHOD (PEMBELAJARAN BERBASIS PEMECAHAN KASUS) DITINJAU DARI KEMAMPUAN KOLABORATIF MAHASISWA - Asri Fauzi; Ida Ermiana; Awal Nur Kholifatur Rosyidah; Muhammad Sobri (Universitas Labuhanbatu, 2022)
The goal to be achieved in this study is to determine the effectiveness of the implementation of the case method (case-solving-based learning) in terms of students' collaborative abilities. This type of research is a quasi-experimental study with the research subjects used as many as 29 PGSD students at the University of Mataram. The instrument of this research used a questionnaire on student collaborative abilities totaling 25 statements with a Likert scale of 1 to 4. The questionnaire was given to students twice, namely before and after learning using the case method. The data analysis technique in this study is the normality test as a prerequisite test, the t-test to determine the difference in the average pretest and posttest collaborative questionnaires, and the N-Gain score test to conclude. The results of this study indicate that the implementation of the case method is effective in terms of students' collaborative abilities.Keywords: case method, collaborative ability.